The Correlation between Serum C3 and C4 Complement Levels with Disease Activity Systemic Lupus Eritematosus Patients In Dr. Soetomo Hospital, Surabaya - Istiana Hairiah Abas; Betty Agustina Tambunan; Awalia Awalia (Current Internal Medicine Research and Practice Surabaya Journal, 2021)
Introduction: The Systemic lupus erythematosus (SLE) is autoimmune disease that results in inflammation, and tissue damage. SLE often creates difficulties in the diagnosis and assessment of disease activity. Disease activity is important as basis for selecting the appropriate therapy. In addition to clinical SLE, supporting investigations are needed to determine disease activity, one of which is complement examination. Complement plays an important role in autoimmune disease and thought to mediate tissue damage. This study aimed to analyze correlation between serum complement C3 and C4 levels with disease activity of SLE patients in Dr. Soetomo Hospital Surabaya.Methods: This study used an observational analytic method with a cross-sectional design. The sampling technique was consecutive sampling. The samples of this study were SLE patients who were treated in the inpatient room and poly rheumatology in January-December 2018 periods. The data were analyzed statistically using the Pearson test.Results: There were 150 SLE patients, most of whom were women (90.0%) with mean age of 29.01±9.8 years. Most levels of complement were low levels (C3 = 48.0% and C4 = 50.7%). Most disease activities were severe flares (44.7%). Results of the Pearson test complement C3 with disease activity were p =0.001, and level of correlation was r =-0.287. However, results of the Pearson test complement C4 with disease activity were p =0.026, and level of correlation was r =-0.182.Conclusion: There is negative correlation between C3 and C4 complement levels with disease activity of SLE patients in Dr. Soetomo Hospital, Surabaya which is significant, weak and opposite.